Pengaruh Komisaris Independen dan Struktur Kepemilikan Terhadap Penerimaan Opini Audit Going Concern : Keywords: Independent Comissioner; Managerial Ownership; Institusional Ownership; Going Concern Audit Opinion. - Asti Wardani; Made Dudy Satyawan (Jurnal Akuntansi, 2022)
This study aims to examine the effect of independent comissioner, managerial ownership, and institutional ownership on acceptance of going concern audit opinion. This paper used mining company from IDX (Indonesia Stock Exchange). Based on quantitative research methods with purposive sampling technique, there are 27 companies as samples of this paper during 2013-2017. Logistic Regression with SPSS 23 was used to analyze the data of this study. The result of this research showed that independent comissioner has negative effect on acceptance of going concern audit opinion, managerial ownership and institutional ownership has no effect on acceptance of going concern audit opinion.Keywords: Independent Comissioner; Managerial Ownership; Institusional Ownership; Going Concern Audit Opinion.